Banking Policy and the Pricing of Deposit Guarantees : A New Approach - Perraudin, W. (IMF Working Papers; Working Paper ;, 1991)
This paper describes a new approach to pricing government deposit guarantees that uses techniques of stochastic process switching employed in the recent literature on exchange rate determination. Our model avoids inconsistent assumptions about the information available to investors and the government common in previous work based on an option pricing approach. We derive actuarially fair deposit insurance premia and optimal financial reorganization rules and examine the role of banking policies such as capital requirements.